O serviço de atendimento à rede de escolarização hospitalar do Hospital Universitário do Oeste do Paraná de Cascavel - Pr: um estudo sobre os adolescentes atendidos na ala de desintoxicação - Mares, Thaise Fernanda de Lima (2016)
The process of education of children and adolescents can be interrupted for many reasons, among which stands out the hospitalization. To attend the children and adolescents hospitalized, whether are they registered or not in school, it was established in 2007 by the Education State Secretariat of Paraná - SEED-PR, through the Secretarial Resolution No. 2,527 / 2007, the Attendance Service to the Hospital Schooling Network - SAREH. In 2011, SAREH was implemented at the University Hospital of Western Parana - HUOP, in Cascavel - PR, to meet students enrolled or not in the school system. Being so, this thesis answers the following problem: What are the limits and possibilities for the educational and administrative processes developed by the Attendance Service to the Hospital Schooling Network in the Detoxification Ward at the HUOP Cascavel - PR, in order to continue the hospitalized students‟ educational process and maintain their link with the school environment? The overall objective, therefore, is to present the educational and administrative processes developed by the SAREH in the Detoxification Ward at the HUOP Cascavel - PR, aiming to analyze the limits and possibilities related to the continuity of the learning process and the maintenance of the link with the school environment of hospitalized students. The specific objectives are: a) Understand the emergency context of the SAREH from the State's relationship with the Social and Educational Policies; b) Identify the social, economic and educational profile of adolescents attended by the SAREH in the Ward Detoxification of HUOP Cascavel-PR from 2011 to 2013; c) present the educational and administrative processes developed in the Detoxification Ward by SAREH of HUOP Cascavel - PR, from 2011 to 2016, aiming to analyze the limits and possibilities for the continuity of the learning process and the maintenance of the link with the school environment of hospitalized students, through interviews with SAREH professionals who work or worked in that wing. It was possible to conclude, through bibliographical, documental and field research, the limits, challenges and possibilities of the SAREH developed in the Detoxification Ward. It was concluded, above all, that the SAREH is part of the Social and Educational Policy and therefore represents the distribution of socially produced wealth. The SAREH, while it is a focused social and educational policy, constitutes the possibility of intervention in the problem of drug addiction and educational services to adolescents admitted to the Detoxification Ward. It has, on the one hand, the scale of social and educational responsibility for covering education and health services. On the other hand, it maintains the perspective of the liberal principles of individuality and freedom, making the adolescents responsible for their actions and for the situation in which they are found, whether it is the use of drugs or the return to school.